Coomb's negative cold agglutinin disease: A rare report of an incidentally detected case - K V Vinu Balraam (Wolters Kluwer Medknow Publications, 2021)
Cold agglutinin disease (CAD) is a rare type of autoimmune hemolytic anemia which usually results due to production of immunoglobulin M-type autoantibody against the I/i and H antigens on red blood cell membrane. They can be idiopathic or may be due to underlying lymphoproliferative disorders or atypical infections. It can have a varied presentation ranging from being incidentally detected to being totally transfusion dependent for a longer or shorter duration. Several factors play a role in determining the ability of cold agglutinins in inducing hemolysis such as antibody concentration and temperature. Here, we present a 54-year-old patient, a known case of chronic obstructive pulmonary disease who was admitted to our hospital in the winter months as a case of alcohol withdrawal syndrome. During the course of the stay, the patient developed respiratory insufficiency and went into Type II respiratory failure and hematological investigations revealed features of CAD.